2006
DOI: 10.1007/s10681-006-9151-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Combining Ability of Petal Shape in Garden Pansy (Viola × wittrockiana Gams) based on Image Analysis

Abstract: Flower appearance is an important target for improvement in garden pansy (Viola × wittrockiana Gams). Flowers of this species consist of three petal types: inferior, lateral, and superior. By means of principal-components (PC) analysis of elliptic Fourier descriptors (EFDs), we estimated the general and specific combining abilities (GCA and SCA) of the floral characteristics of F 1 progeny derived from diallel crosses of four inbred lines. The greatest variation in petal shape was explained by the aspect ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…In this study, we observed that the leaf area and stomata and flower size of the V. •wittrockiana inbred lines were increased significantly compared with the V. cornuta inbred line, but we observed no distinct differences in leaf shape corresponding to the leaf index between the V. •wittrockiana inbred and the V. cornuta lines. In V. •wittrockiana, additive genetic variance in the transmission of parental petal characteristics (superior and lateral petal ratio and area) to the progeny is extremely important and should be taken into account by breeders (Yoshioka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that the leaf area and stomata and flower size of the V. •wittrockiana inbred lines were increased significantly compared with the V. cornuta inbred line, but we observed no distinct differences in leaf shape corresponding to the leaf index between the V. •wittrockiana inbred and the V. cornuta lines. In V. •wittrockiana, additive genetic variance in the transmission of parental petal characteristics (superior and lateral petal ratio and area) to the progeny is extremely important and should be taken into account by breeders (Yoshioka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pansy is one of the most colorful flowers around the world, success of artificial hybridization among intra-and interspecific by many breeders since the 19th century (Yoshioka et al 2006, Li et al 2014, Du et al 2018). However, little information about pansy flower color measured by colorimeter has been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Shape analysis of leaves has used scanned images, for apple, grapevine, Claytonia L., and a mixture of species [2,3,4,5] 1 . Scanners have also been used to analyze the shape of pansy petals [6] and Vitis vinifera L. seeds [7].…”
Section: Introductionmentioning
confidence: 99%